2012
DOI: 10.1177/0020764012456807
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated illness (DUI) and schizophrenia sub-types: A collaborative study between the universities of Milan and Moscow

Abstract: The results of the present study suggest that the different schizophrenic sub-types may differ in terms of DUI, likely due to different clinical severity and social functioning. Studies with larger samples are needed to confirm the data of the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…DUI is a clinical variable of great interest in clinical practice because, unlike many other factors, it is modifiable by providing early diagnosis and treatment to the patient. It is well established that a prolonged DUI is associated with a poorer outcome not only in schizophrenia (Buoli et al, 2013), but also in mood disorders (Altamura et al, 2007), anxiety disorders (Altamura, Dell'osso, D'Urso, et al, 2008;Dell'Osso, Camuri, Benatti, Buoli, & Altamura, 2013) and obsessive-compulsive disorder(Dell'Osso, Buoli, Hollander, & Altamura, 2010). In our study, the average DUI was lower than that reported by most studies in the field, but consistent with the constant reduction of DUI over epochs of time observed in recent reports (Dell'Osso et al, 2016)(Dell'Osso et al, 2017, 2016.…”
Section: Discussionsupporting
confidence: 90%
“…DUI is a clinical variable of great interest in clinical practice because, unlike many other factors, it is modifiable by providing early diagnosis and treatment to the patient. It is well established that a prolonged DUI is associated with a poorer outcome not only in schizophrenia (Buoli et al, 2013), but also in mood disorders (Altamura et al, 2007), anxiety disorders (Altamura, Dell'osso, D'Urso, et al, 2008;Dell'Osso, Camuri, Benatti, Buoli, & Altamura, 2013) and obsessive-compulsive disorder(Dell'Osso, Buoli, Hollander, & Altamura, 2010). In our study, the average DUI was lower than that reported by most studies in the field, but consistent with the constant reduction of DUI over epochs of time observed in recent reports (Dell'Osso et al, 2016)(Dell'Osso et al, 2017, 2016.…”
Section: Discussionsupporting
confidence: 90%
“…10,11 To date, DUI has been investigated across different psychiatric conditions, including major depressive disorder (MDD), 12,[13][14][15] bipolar disorder, 16 obsessive-compulsive disorder (OCD), [17][18][19] somatization, 20 eating, 21 and schizophrenia spectrum disorders. 8,[22][23][24] In respect to anxiety disorders, previous reports indicate a significantly shorter DUI compared to findings from studies conducted with patients with obsessive-compulsive, mood, and schizophrenia spectrum disorders. 9,25,26 Moreover, differences in terms of latency to treatment emerged between patients with PD and generalized anxiety disorder, with PD patients having a shorter DUI.…”
Section: Introductionmentioning
confidence: 85%
“…Of note, in our analyses the duration of illness refers to the duration of substance use disorder, and the duration of untreated illness (DUI) is defined as the time between the onset of psychotic symptoms and the administration of an antipsychotic compound [ 32 ].…”
Section: Methodsmentioning
confidence: 99%